Critical integrated marketing communication dimensions driving enrollment in Vietnam’s higher education sector - Nguyen, Thao T T; Le, Tri D; Tran, Khoa T; Nguyen, V P (International Journal of Innovative Research and Scientific Studies, 2025)
The emergence of integrated marketing communication (IMC) is progressively relevant to Vietnam's higher education sector, which comprises over two million students, while international enrollment continues to grow. Based on that premise, this study critically investigates IMC-induced student enrollment, filling seemingly uncharted territory in non-Western higher education marketing research. The study relied on a mixed-methods convergent parallel design wherein qualitative data derived from in-depth interviews with ten marketing experts from public and private higher education institutions (HEIs) were integrated with quantitative data comprising enrollment statistics (2019-2024) of these HEIs and survey responses from 128 stakeholders (75 marketing managers, 37 students, 38 parents). The analysis revealed that the most important IMC practices included digital channels (e.g., social media, websites), high school teacher networks, and organizational integration. Results of the survey corroborated this finding, as social media content (M=4.3) and websites (M=4.1) were rated highest in effectiveness on a 5-point Likert scale. The factor analysis further validated four dimensions interacting with each 28% variance: Consistency (22%), Stakeholder Integration (19%), and Measurable Results (17%) and accounts for 86% variance. Enrollment data showed that seven high-performing HEIs had a mean growth rate of 10.5%, while 15-18% spikes after digital campaigns showed the difference between high-performing and low-performing HEIs (n=3). The results imply that the digital IMC transforms, reconceptualizes the value in stakeholder networks, and demonstrates the need for organizational internal alignment. The study notably extends the IMC constructs to emerging markets in theory and, in practical terms, advocates market-specific digital strategies and multipronged performance metrics for HEI managers. Future research should consider longitudinal effects and more stakeholders to further improve IMC applications in higher education marketing.